Fallokracja czy waginocentryzm? Głos feministek we współczesnej debacie o płci, języku i kulturze - Mrosik, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Since the very beginning, feminism has been surrounded by numerous legends, myths and not-quite-credible stories that generally stem from the miscomprehension of its ideas. It still continues to be presented in a caricatured and stereotypical manner. The media have a considerable share in creating such attitudes to feminism, as they construct the majority of their accounts of the feminist movement around the „interrelated activities of an antagonist and protagonist”. The search for the common nature of feminine experience faces numerous obstacles. These involve political and social ones (differences of race, class, religion, sexual orientation, etc.); the identity of the subject- woman has not been agreed; the attempts to establish feminine language fail. It is increasingly questioned whether this manner of presenting feminism in the media is not becoming a new form of exclusion – a new form of Differentness.